Performance and emission assessment of multi cylinder diesel engine using surfactant enhanced water in diesel emulsion - Khan, M.Y. (EDP Sciences, 2014)
A four stroke, four cylinder, In-direct injection diesel engine was used to study the effect of emulsified diesel fuel with 5 water by volume on the engine performance and on the main pollutant emissions. The experiments were conducted in the speed range from 1000 to 4500 rpm at full load conditions. It was found that, in general, using emulsified fuel improves the engine performance with slight increase in emissions. While the BSFC has a minimum value for 5 water and at all rpm, the torque, the power and the BMEP are found to have maximum values under these conditions when compared conve ntional disel. CO2 was found to increase with engine speed whereas increase in CO and NOX were minimum. In this work water in diesel emulsion was prepared by a mechanical homogenizer and their physical and chemical properties were examined. Â© 2014 Owned by the authors, published by EDP Sciences.